Diversity and dynamics of bacterial communities in the drinking water distribution network of a mid-sized city in Brazil. (17th November 2022) - Batista, Ana Maria Moreira; Siqueira, Juliano Curi de; Meynet, Paola; Werner, David; Garcia, Graziella Patricio Pereira; Davenport, Russell J.; Pereira, Alyne Duarte; Siniscalchi, Luciene Alves Batista; Araújo, Juliana Calábria de; Mota Filho, Cesar Rossas
Abstract: This study assessed the bacterial community composition of a drinking water system (DWS) serving a mid-sized city (120, 000 inhabitants) in Brazil. Water samples, including raw and treated water, were collected at seven points throughout the DWS. DNA was extracted and analysed using high-throughput sequencing (Ion Torrent). Free chlorine and turbidity were measured in situ . Results showed that the highest relative abundance of 16S rRNA genes was from phyla Proteobacteria, followed by Bacteroidetes and Actinobacteria. The next most abundant phylum was Cyanobacteria, represented by Arthronema, Calothrix, and Synechococcus. An interesting observation was that the DNA-based analysis suggested a bacterial community change in the distribution network, with treated reservoir water being very different from the network samples. This suggests active microbiology within the distribution network and a tendency for bacterial diversity to decrease after chlorine disinfection but increase after pipeline distribution. In raw water, a predominance of Proteobacteria was observed with reduced Cyanobacteria, showing a negative correlation. In treated water, Proteobacteria were negatively correlated with Bacteroidetes. Finally, 16S rRNA genes from Firmicutes (especially Staphylococcus ) had a high abundance in the chlorinated water, which may indicate the phylum's resistance to chlorine residuals. Opportunistic pathogens, e.g., Mycobacteria, Legionella, and Staphylococcus, were also observed. HIGHLIGHTS: Next-generation sequencing (NGS) revealed substantial changes in microbiota from a small drinking water system (DWS) after disinfection. Proteobacteria, Bacteroidetes, Actinobacteria, and Cyanobacteria had high abundance. Firmicutes in the chlorinated water may indicate resistance to chlorine residuals. The chlorinated water sample presented opportunistic pathogens. Environmental degradation may have led to bioremediation species' growth. Graphical Abstract